ESTIMATING FUNCTION SUPPLY FOR RED MEAT IN IRAQ FOR THE PERIOD 1995-2013 - & Al-Hani, Ahmad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Red meat production is an essential and important in the amount of livestock production part and contribute to livestock about 22% of the value of agricultural production, except fish in Iraq over the medium term from 2013 to 2009,The red meat and meat products of are consider good foods with a high nutritional value because they contain vitamins, proteins, fats and minerals .So it requires such a study to estimate the function supply red meat to a statement most influential variables in the supply quantity of red meat during the period 1995-2013 It is clear from the results that the rise in red meat prices by 1% leads to increase the quantity supplied of red meat increased by 0.403%, while the increase of chicken meat prices by 1% leads to a decline in the quantity supplied of red meat increased by 0.327%, while increasing the number of animals by 1 % leads to increase the quantity supplied of red meat increased by 23.267%, while the increase of imported red meat quantity of 1% lead to a decline in the quantity supplied of red meat increased by 0.007 and through the price elasticity of supply became clear that the display of red meat is flexible and elastic modulus less than the one . Through flexibility Cross turned out to be chicken meat is the alternative to red meat. Finally, the study included a number of conclusions and recommendations of the most important: by measuring the consumption growth rate of 10% and the rate of production growth of 7% and it can be concluded that production covers a large part of consumption. The study recommended that there is a gap between the production and import recommenddirect loans to invest in the livestock sector.